Corrigendum: Tomographic characterization of copper cellular bodies fabricated by a powder metallurgy route (2019 Mater. Res. Express 6 056531) - Malachevsky, Maria Teresa; Bertolino, Graciela Mabel; Oliber, Edgardo Antonio; D'ovido, Claudio; Baruj, Alberto Leonardo; Cuscueta, Diego Javier (IOP Publishing, 2021)
Fil: Malachevsky, Maria Teresa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina